A physiological and biomechanical investigation of three passive upper-extremity exoskeletons during simulated overhead work. Issue 1 (2nd January 2022) - Weston, Eric B.; Alizadeh, Mina; Hani, Hamed; Knapik, Gregory G.; Souchereau, Reid A.; Marras, William S.
Abstract: The objective of this study was to evaluate three passive upper-extremity exoskeletons relative to a control condition. Twelve subjects performed an hour-long, simulated occupational task in a laboratory setting. Independent measures of exoskeleton, exertion height (overhead, head height), time, and their interactions were assessed. Dependent measures included changes in tissue oxygenation (ΔTSI) in the anterior deltoid and middle trapezius, peak resultant lumbar spine loading, and subjective discomfort in various body regions. A statistically significant reduction in ΔTSI between exoskeleton and control was only observed in one instance. Additionally, neither increases in spinal loading nor increases in subjective discomfort ratings were observed for any of the exoskeletons. Ultimately, the exoskeletons offered little to no physiological benefit for the conditions tested. However, the experimental task was not highly fatiguing to the subjects, denoted by low ΔTSI values across conditions. Results may vary for tasks requiring constant arm elevation or higher force demands. Practitioner summary This study quantified the benefits of upper-extremity exoskeletons using NIRS, complementary to prior studies using EMG. The exoskeletons offered little to no physiological benefit for the conditions tested. However, the experimental task was not highly fatiguing, and results may vary for an experimental task with greater demand on the shoulders. Abbreviations: WMSD: work-related musculoskeletal disorder; EMG: electromyography; NIRS: near-infrared spectroscopy; NIR: near-infrared; Hb: haemoglobin; Mb: myoglobin; TSI: tissue saturation index; ATT: adipose tissue thickness